2015
DOI: 10.1038/nature14546
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rescue in pluripotent cells from patients with mtDNA disease

Abstract: Mitochondria have a major role in energy production via oxidative phosphorylation, which is dependent on the expression of critical genes encoded by mitochondrial (mt)DNA. Mutations in mtDNA can cause fatal or severely debilitating disorders with limited treatment options. Clinical manifestations vary based on mutation type and heteroplasmy (that is, the relative levels of mutant and wild-type mtDNA within each cell). Here we generated genetically corrected pluripotent stem cells (PSCs) from patients with mtDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(195 citation statements)
references
References 30 publications
(37 reference statements)
13
182
0
Order By: Relevance
“…Studies have indicated that the induction to iPSCs may be associated with heteroplasmic mtDNA alterations (Folmes et al, 2013;H€ am€ al€ ainen et al, 2013;Perales-Clemente et al, 2016;Prigione et al, 2011b). These variations appear to derive from the clonal origin of the iPSCs, because they also occur in clonally expanded fibroblasts (Kang et al, 2016;Ma et al, 2015). This means that the mtDNA sequence profile of patient-derived iPSC lines must be thoroughly assessed to ensure that the cells are suitable for use in drug discovery or other types of treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that the induction to iPSCs may be associated with heteroplasmic mtDNA alterations (Folmes et al, 2013;H€ am€ al€ ainen et al, 2013;Perales-Clemente et al, 2016;Prigione et al, 2011b). These variations appear to derive from the clonal origin of the iPSCs, because they also occur in clonally expanded fibroblasts (Kang et al, 2016;Ma et al, 2015). This means that the mtDNA sequence profile of patient-derived iPSC lines must be thoroughly assessed to ensure that the cells are suitable for use in drug discovery or other types of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…To make useful models of mitochondrial diseases from NI NPCs, we needed to exclude the possibility that mtDNA had undergone changes during stages of induction, as can happen in the generation of iPSCs (Ma et al, 2015;Prigione et al, 2011b). We performed Sanger sequencing of the entire mtDNA, using long-range PCR with nested primers to exclude nuclear mtDNA pseudogenes.…”
Section: Ni Npcs Retain Their Parental Mtdna Sequence Profilementioning
confidence: 99%
“…Research gamete donors were financially compensated for their time, effort, discomfort, and inconvenience associated with the donation process at rates similar to donors whose gametes were used for reproductive purposes. This specific IRB protocol was first approved in 2011 and then reviewed annually with modifications allowing the development, evaluation and testing, in vitro, of novel mitochondrial replacement techniques (see Data S1) (Kang et al, 2016;Ma et al, 2015;Tachibana et al, 2013a;Tachibana et al, 2013b).…”
Section: Gamete Donationmentioning
confidence: 99%
“…The prospect of something similar in humans would potentially address carryover by enabling the isolation of patient-derived iPS cell lines that contained no affected mitochondria, either by selection or manipulation, and the recapitulation of meiosis from these lines to yield oocytes. Indeed, iPS cell lines containing exclusively wild-type mtDNA have previously been derived through spontaneous segregation from patients with Leigh syndrome and MELAS 69 . However, extrapolating in vitro oogenesis protocols from mouse to human is unlikely to be trivial; in vitro maturation (IVM) of immature oocytes to produce fertilizable oocytes in the mouse 70 took over two decades to translate to IVM in humans 71 .…”
Section: Mitophagymentioning
confidence: 99%